2019
DOI: 10.1088/1757-899x/578/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Graphene Oxide/Calcium Carbonate/Chitosan Nanocomposite Film with Enhanced Mechanical Properties

Abstract: Nanocomposites are an attractive field of materials providing novel performance owing to their remarkable properties at low filler loading. Currently, they are being increasingly used by industry whilst displacing the use of conventional filler materials. A lot of nanoscale fillers are capable to enhance mechanical and thermal properties of nanocomposites. Graphene, a single layer of carbon atoms in a hexagonal lattice, has recently attracted much attention due to their novel electronic and mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Based on the study, the diffraction peak for GO is 10.7° while the diffraction peak for graphite is 26.6° [32]. It can be concluded that in the sample, there is completely oxidized after treatment of the oxidation and exfoliation of graphite resulted the formation of oxygen-containing functional groups of graphene oxide [33,34] The XRD results of rGO/AgNPS is shown in Fig. 1.…”
Section: Discussion Of Synthesis Of Nanocomposites Reduced Graphene O...mentioning
confidence: 89%
“…Based on the study, the diffraction peak for GO is 10.7° while the diffraction peak for graphite is 26.6° [32]. It can be concluded that in the sample, there is completely oxidized after treatment of the oxidation and exfoliation of graphite resulted the formation of oxygen-containing functional groups of graphene oxide [33,34] The XRD results of rGO/AgNPS is shown in Fig. 1.…”
Section: Discussion Of Synthesis Of Nanocomposites Reduced Graphene O...mentioning
confidence: 89%
“…Following our previous procedure, we synthesized graphene oxide (GO) using Hummer's method [42][43][44][45]. The synthesis was started by mixing 0.5 g of sodium nitrate, 2.5 g of potassium permanganate, 0.5 g of graphite, and 23.3 ml of H 2 SO 4 .…”
Section: Graphene Oxide (Go) Synthesismentioning
confidence: 99%